If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 75) = (4x + -25) Reorder the terms: (75 + 2x) = (4x + -25) Remove parenthesis around (75 + 2x) 75 + 2x = (4x + -25) Reorder the terms: 75 + 2x = (-25 + 4x) Remove parenthesis around (-25 + 4x) 75 + 2x = -25 + 4x Solving 75 + 2x = -25 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 75 + 2x + -4x = -25 + 4x + -4x Combine like terms: 2x + -4x = -2x 75 + -2x = -25 + 4x + -4x Combine like terms: 4x + -4x = 0 75 + -2x = -25 + 0 75 + -2x = -25 Add '-75' to each side of the equation. 75 + -75 + -2x = -25 + -75 Combine like terms: 75 + -75 = 0 0 + -2x = -25 + -75 -2x = -25 + -75 Combine like terms: -25 + -75 = -100 -2x = -100 Divide each side by '-2'. x = 50 Simplifying x = 50
| 1+2(5x-3)=-2(6x-5)+4x | | (4x+18)=(7x-72) | | 4t^2-14t+35=0 | | -3X+7=-2X+4 | | 3/8*x=21/2 | | 4g+3=1g | | 3-2x=1000x | | 37w^2-312w-192924=0 | | (82.4-52)3/5=x | | -5X+13=-3X+7 | | (84.4-52)3/5=x | | z+72=8 | | 21X-39=13X-23 | | -11X-85=-6X-45 | | 6X-43=3X-22 | | 12X+134=6X+80 | | 3ln(x)+8=ln(3x)+12 | | 4psquared-12p+7=0 | | 45logx=3 | | 10X+36=6X+20 | | 34-9k=88 | | -5X-40=-3X-26 | | 2x^2-25x+80=0 | | -(3w+4)+5(w-2)-3(6w-8)=1 | | (x+35)=(3x+5) | | 10x^2+9x-117=0 | | 3x+8=4x-10 | | 10x^2+9x-108=0 | | -2x^2+54x=0 | | 6(y-6)/10(y-6) | | H(5x)=3x^2+2 | | 2x^2+52x=0 |